Teaching methodology impact on students’ understanding and knowledge retention: students’ perspective / Nur Adila Nasir - Nasir, Nur Adila (2012)
The present study explores final year pharmacy students’ perception on teaching methodology’s implications towards their understanding and knowledge retention. The purpose of this study is to evaluate which teaching methodology is preferred by students where they feel can enhance their understanding and knowledge retention. In this study, Cumulative Grade Point Average (CGPA) was used to objectively measure knowledge retention. A cross sectional quantitative surveys were conducted amongst UiTM final year pharmacy students with a self developed questionnaire and Myers-Brigg Type Indicator (MBTI). The results showed that effective teaching methods in the clinical course was best defined by problem based learning (PBL) / case based learning (CBL) and different teaching methods, whereas practical based and small group tutorials were most frequently provides impact on students’ understanding and knowledge retention. These findings can provide guidance for lecturers to design better strategies for more effective clinical teaching for undergraduate pharmacy students. It is hope that the results from this study will be a catalyst for future academic effort in bringing current clinical teaching to a new paradigm.